Weryfikacja systemu wczesnego ostrzegania o niekorzystnym poziomie płynności finansowej - Szpulak, Aleksandra (Verification of Early Warning System of Adverse Corporate Liquidity Level, 2007)
This article contains two parts - theoretical and empirical. The first one is about early warning system of adverse corporate liquidity level basic rules and the way of measuring accuracy of system's outcome. The second one is devoted to measure accuracy of outcome generated by early warning system, which was applied into Polish producing companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 536-549